Penegakan Hukum Lingkungan Bidang Pertambangan Batubara dan Penguatan Lembaga Masyarakat Adat - Afif Syarif; Eko Nuriyatman (Universitas Batanghari Jambi, 2020)
This scientific article discusses the enforcement of environmental law in the field of coal mining and the strengthening of indigenous community institutions in Bungo Regency. The research approach method used in this scientific article is normative juridical and empirical juridical to be able to find the concept of enforcement of environmental law in the field of coal mining by examining the principles of mining law for the welfare of the community. The nature of environmental law should be able to prevent the occurrence of pollution and environmental damage and the existence of institutions of indigenous peoples in Bungo District has not functioned in the enforcement of environmental law in the field of coal mining business. Therefore the Bungo District government needs to strengthen the institutional of indigenous peoples so that it can function to enforce environmental law against coal mining to improve the welfare of the people in Bungo District.